2017
DOI: 10.1136/tobaccocontrol-2017-053920
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of compliance with national comprehensive smoke-free laws

Abstract: The results show the importance of the depth of the enforcement infrastructure and effort represented by the degree to which the local government is involved in enforcement. They also show the significance of fighting corruption in the enforcement process, including the attempts of the tobacco industry to undermine the process, to achieve high levels of compliance with the law. The results point out to the need to invest minimal but essential enforcement resources given that national comprehensive smoke-free l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Greece, where regulation on e-cigarette use came into force in 2010 (Law 3868/2010) 28 , is the country with the highest prevalence of observed e-cigarette use in public places and reported SHA exposure. This may reveal other hidden aspects hindering adherence to current legislation, such as low level of enforcement and penalties application, degree of local government involvement, and tobacco industry investment in novel tobacco products 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Greece, where regulation on e-cigarette use came into force in 2010 (Law 3868/2010) 28 , is the country with the highest prevalence of observed e-cigarette use in public places and reported SHA exposure. This may reveal other hidden aspects hindering adherence to current legislation, such as low level of enforcement and penalties application, degree of local government involvement, and tobacco industry investment in novel tobacco products 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…A multinational study showed that high compliance with comprehensive smoke-free laws was associated with robust local enforcement activities. 62 Current enforcement of POS policies in India appears to lack coordination and is inconsistent. 63 The Government of India Ministry of Health has the central enforcement authority, but improvements in communication and coordination between the federal Ministry and local agencies is needed, for example, identification of local enforcement agencies like health ministries, police departments and schools.…”
Section: Discussionmentioning
confidence: 99%
“…Although only limited research has been conducted, some studies investigated factors associated with achieving high compliance of national smoke-free laws. For example, compliance with national smoke-free laws was positively associated with government involvement (training and guidelines for inspections) and perceived corruption control [11].…”
Section: Discussionmentioning
confidence: 99%